A NEW METHOD FOR RECORDING THE RESPIRATORY MOVEMENTS OF FISH - Rao, K S R Prasada; Rao, D G V Prasada; Rao, Y Prabhakara; Rao, P Niranjana (Indian Journal of Fisheries, 2011)
A new method has been developed using the LDR system for recordingthe respiratory movements in fish, employing which the effect of toxicants on therespiratory movements can be studied.